Effect Of Dragon Fruit Juice (Hylocereus Polyrhizus) On Xanthine Oxidase Activity And Blood Nitric Oxide Levels On Rats With Hyperuricemia - Riska Yulia Pratiwi; Achmad Zulfa Juniarto (Universitas Aisyah Pringsewu, 2022)
Hyperuricemia, the condition when serum uric acid level is above normal value, is not only a risk factor for the occurrence of gout, but also the incidence of cardiovascular disease. Red dragon fruit (Hylocereus polyrhyzus) are rich in flavonoids which have the potential as antihyperuricemia. This study aims to prove the effect of red dragon fruit to hyperuricemic rats on the activity of the xanthine oxidase enzyme and the levels of nitric oxide (NO). The method used is a true-experimental randomized pre-post with control group design. The hyperuricemic rats treating with broth blocks and potassium oxonate. The sample in this study consisted of thirty Wistar rats (Rattus norvegicus) were divided into 6 groups: healthy control (K0), hyperuricemic control (K1), and treatment groups (K2, K3, K4, K5). The intervention was given for 28 days with allopurinol 1.8 mg.200g-1 rat’s BW and red dragon fruit juice intervention dose of 6 gr.200g-1 rat’s BW, 12 gr.200g-1 rat’s BW and 18 gr.200g-1 rat’s BW. Uric acid levels, XO activity, and NO levels were measured using FS TBHBA method, Xanthine Oxidase Chekinetm Assay Kit, and Nitric Oxide (NO) Colorimetric Assay Kit. The difference in increased UA levels and the smallest XO activity indicated by the K2 group (p less than 0.05), the smallest degree of decreasing the small number is shown by the K5 group (p less than 0.05) compared to the K0 and K1 groups (p less than 0.05). The K5 group has the most effective dose in preventing hyperuricemia and maintaining NO levels 140 mg.200g-1 rat’s body weight. Abstrak: Hiperurisemia, suatu kondisi di mana kadar serum asam urat darah di atas normal, tidak hanya menjadi faktor resiko arthritis gout, namun juga faktor resiko penyakit kardiovaskuler. Buah Naga Merah / BNM (Hylocereus polyrhyzus) kaya akan flavonoid yang berpotensi sebagai antihiperurisemia. Penelitian ini bertujuan untuk membuktikan pengaruh pemberian jus BNM (Hylocereus polyrhizus) pada tikus hiperurisemia, dilihat dari aktivitas enzim xanthine oxidase dan kadar nitric oxide (NO). Metode yang digunakan ialah a true-experimental randomized dengan pre-post control group design. Tikus diinduksi dengan kaldu blok dan potasium oksonat. Sampel pada penelitian ini berjumlah tiga puluh ekor tikus Wistar (Rattus norvegicus) yang dibagi menjadi 6 kelompok perlakuan, yaitu kontrol negatif (K0), kontrol positif (K1), dan kelompok intervensi (K2, K3, K4, K5). Intervensi diberikan selama 28 hari dengan allopurinol 1,8 mg/200 g BB/hari dan intervensi jus BNM (Hylocereus polyrhizus) dosis 6 gr/200 gr BB, 12 gr/200 gr BB dan 18 gr/200 gr BB. Kadar asam urat serum, aktifitas XO, dan kadar NO diukur dengan metode FS TBHBA, CheKineTM Xanthine Oxidase Assay Kit, dan Nitric Oxide (NO) Colorimetric Assay Kit. Peningkatan kadar AU dan aktifitas XO paling kecil ditunjukkan oleh kelompok K2 (p kurang dari 0,05), selisih penurunan kadar NO paling kecil ditunjukkan oleh kelompok K5 (p kurang dari 0,05) dibandingkan kelompok K0 dan K1 (p kurang dari 0,05). Kelompok K5 memiliki dosis yang paling efektif dalam mencegah terjadinya hiperurisemia dan menghambat penurunan kadar NO.